Transcriptome analysis reveals effects of leukemogenic SHP2 mutations in biosynthesis of amino acids signaling - Zhao, Yuming; Chang, Zhiguang; Hu, Bingbing; Zhang, Qi; Zhang, Dengyang; He, Chunxiao; Guo, Yao; Peng, Zhiyong; Chen, Chun; Chen, Yun (Frontiers in Oncology, 2023)
Gain-of-function mutations of SHP2, especially D61Y and E76K, lead to the development of neoplasms in hematopoietic cells. Previously, we found that SHP2-D61Y and -E76K confer HCD-57 cells cytokine-independent survival and proliferation via activation of MAPK pathway. Metabolic reprogramming is likely to be involved in leukemogenesis led by mutant SHP2. However, detailed pathways or key genes of altered metabolisms are unknown in leukemia cells expressing mutant SHP2. In this study, we performed transcriptome analysis to identify dysregulated metabolic pathways and key genes using HCD-57 transformed by mutant SHP2. A total of 2443 and 2273 significant differentially expressed genes (DEGs) were identified in HCD-57 expressing SHP2-D61Y and -E76K compared with parental cells as the control, respectively. Gene ontology (GO) and Reactome enrichment analysis showed that a large proportion of DEGs were involved in the metabolism process. Kyoto Encyclopedia of Gene and Genome (KEGG) pathway enrichment analysis showed that DEGs were the mostly enriched in glutathione metabolism and biosynthesis of amino acids in metabolic pathways. Gene Set Enrichment Analysis (GSEA) revealed that the expression of mutant SHP2 led to a significant activation of biosynthesis of amino acids pathway in HCD-57 expressing mutant SHP2 compared with the control. Particularly, we found that ASNS, PHGDH, PSAT1, and SHMT2 involved in the biosynthesis of asparagine, serine, and glycine were remarkably up-regulated. Together, these transcriptome profiling data provided new insights into the metabolic mechanisms underlying mutant SHP2-driven leukemogenesis.